Future impact of non-land based traffic emissions on atmospheric ozone and OH - an optimistic scenario and a possible mitigation strategy - Hodnebrog, O.; Berntsen, T. K; Dessens, O.; Gauss, M.; Grewe, V.; Isaksen, I. S. A; Koffi, B.; Myhre, G.; Olivie, D.; Prather, M. J; Pyle, J. A; Stordal, F.; et al. (Atmospheric Chemistry and Physics, 2011)
The impact of future emissions from aviation and shipping on the atmospheric chemical composition has been estimated using an ensemble of six different atmospheric chemistry models. This study considers an optimistic emission scenario (B1) taking into account e.g. rapid introduction of clean and resource-efficient technologies, and a mitigation option for the aircraft sector (B1 ACARE), assuming further technological improvements. Results from sensitivity simulations, where emissions from each of the transport sectors were reduced by 5%, show that emissions from both aircraft and shipping will have a larger impact on atmospheric ozone and OH in near future (2025; B1) and for longer time horizons (2050; B1) compared to recent time (2000). However, the ozone and OH impact from aircraft can be reduced substantially in 2050 if the technological improvements considered in the B1 ACARE will be achieved. Shipping emissions have the largest impact in the marine boundary layer and their ozone contribution may exceed 4 ppbv (when scaling the response of the 5% emission perturbation to 100% by applying a factor 20) over the North Atlantic Ocean in the future (2050; B1) during northern summer (July). In the zonal mean, ship-induced ozone relative to the background levels may exceed 12% near the surface. Corresponding numbers for OH are 6.0 × 105 molecules cm−3 and 30%, respectively. This large impact on OH from shipping leads to a relative methane lifetime reduction of 3.92 (±0.48) on the global average in 2050 B1 (ensemble mean CH4 lifetime is 8.0 (±1.0) yr), compared to 3.68 (±0.47)% in 2000. Aircraft emissions have about 4 times higher ozone enhancement efficiency (ozone molecules enhanced relative to NOx molecules emitted) than shipping emissions, and the maximum impact is found in the UTLS region. Zonal mean aircraft-induced ozone could reach up to 5 ppbv at northern mid- and high latitudes during future summer (July 2050; B1), while the relative impact peaks during northern winter (January) with a contribution of 4.2%. Although the aviation-induced impact on OH is lower than for shipping, it still causes a reduction in the relative methane lifetime of 1.68 (±0.38)% in 2050 B1. However, for B1 ACARE the perturbation is reduced to 1.17 (±0.28)%, which is lower than the year 2000 estimate of 1.30 (±0.30)%. Based on the fully scaled perturbations we calculate net radiative forcings from the six models taking into account ozone, methane (including stratospheric water vapour), and methane-induced ozone changes. For the B1 scenario, shipping leads to a net cooling with radiative forcings of −28.0 (±5.1) and −30.8 (±4.8) mW m−2 in 2025 and 2050, respectively, due to the large impact on OH and, thereby, methane lifetime reductions. Corresponding values for the aviation sector shows a net warming effect with 3.8 (±6.1) and 1.9 (±6.3) mW m−2, respectively, but with a small net cooling of -0.6 (±4.6) mW m−2 for B1 ACARE in 2050.